PENGARUH METODE EKLEKTIK TERHADAP HASIL BELAJAR KETERAMPILAN BERBICARA BAHASA ARAB SISWA KELAS X MA MANAHIJUL HUDA NGAGEL DUKUHSETI PATI (Lisanul Arab: Journal of Arabic Learning and Teaching, 2012)
Speaking skills is one of the language skills to be achieved in the teaching of modern languages ​​including Arabic. Result of learning the Arabic language subjects in class X in part has not produced the expected results. Based on the results of preliminary studies, it is known that the classical completeness students in mastering the skills of speaking only reached 60%, and the value of minimum completeness criteria in the school for Arabic subjects was 75. So it can be said the value of the average student does not achieve a passing grade in the school competence. On the basis of the survey results it needs continuous efforts to seek and find the method of learning Arabic is able to motivate the students to continue to be active in participating in learning and can improve student learning outcomes. The research problem is How to change students' speaking ability after using the communicative method is eclectic with Arabic speaking skills class X MA Manahijul Huda Ngagel Dukuhseti Starch and How eclectic method influence on Arabic speaking skills class X MA Manahijul Huda Ngagel Dukuhseti Starch .